Uma seqüência de ensino para o estudo de logaritmos usando a engenharia didática. - Ferreira, Ronize Lampert (2006)
This research proposes to check whether the use of a didactic sequence, created according to the stages of the Didactic Engineering, presenting problems concerning real situations, motivating the research and activities related to the appearance of logarithms, it is contributing to the construction of comprehension of the logarithm concept by students. The study is based on didactic of mathematics, which is concerned about experiences results in the classroom related to teaching-learning processes of mathematics subjects. The methodology that was used follows the Didactic Engineering principles, which is justified due to the fact that it is a conception that gives importance to the theoretical dimension as well as to the experiential dimension of the research and whose objective is to analyze the didactic situations, object of study of the mathematics education. The activities of the sequence were elaborated in order to have students from the first grade of high school level, 7 from Colégio Militar de Santa Maria, taking part in the building of the logarithm concept. In this study, the productions of 27 (twenty-seven) students, who were grouped in trios, were analyzed. One can infer from the later analysis that the activities of the sequence contributed to the acquisition of the logarithm concept. The obtained results also showed the classes that were performed at the computer labarotary, using Winplot software, facilitated the construction of exponential and logarithmic function graphics, allowing the development of competences to interpret them as well as the construction of the logarithmic scale. Moroever, the development of the activities related to the teaching sequence made students learn the logarithm concept and the logarithmic scale more significantly, turning it possible for students to use this concept to understand the real world phenomena.